Gerakan 6 Langkah Cuci Tangan Desa Wisata Tingal Kulon, Wanurejo Borobudur - Arlina Dhian Sulistyowati; Kusumaningrum, Puput Risti; Widyaningrum, Sekar; Habibillah, Annisa’ Adhien (WASATHON Jurnal Pengabdian Masyarakat, 2024)
The advancement of the Tingal Kulon Tourism Village in Wanurejo Borobudur is significantly impacted by the community's participation in preserving health in the village. The community plays a pivotal role in safeguarding and advancing the potential present in the Tourism Village. The primary basis for society's ability to carry out daily tasks is health. People may be more susceptible to diseases brought on by the community's own Clean and Healthy Living Behavior (PHBS) or by tourists' visits due to the high volume of visitors to tourist towns from both inside and outside the nation. With PHBS, attempts can be done to preserve health. The purpose of this service is to encourage more people to wash their hands in the Tingal Kulon Wanurejo, Borobudur, Tourism Village. As a result of performing community service, posters and amenities in the Tourism Village neighborhood of Tingal Kulon Wanurejo, Borobudur, were hand washed. People are aware of how important it is to wash their hands in order to stop the spread of illness, and they actively engage in hand washing education. The takeaway from this community service project is that having a hand washing station at Tourism Village, Tingal Kulon Wanurejo, Borobudur, can raise people's knowledge of how important it is to wash their hands.